Les ressorts de l’intervention militaire tchadienne au Mali (2013) - Géraud Magrin (EchoGéo)
This paper analyses the rationale behind the Chadian military intervention in Mali in 2013, which Chad is not a neighboring country, and whereas Chad is not an Ecowas member. We argue that the official reason – preventing Islamist rise into the Sahel – is a secondary one. This Chadian armed intervention takes place in a long soldiering history influenced by a tied but ambiguous relationship with France. It makes possible both to renew a diplomatic rent very useful in a regional disrupt context, to show the regional leadership of the new Chadian petro-State, and to reinforce a regime which stays vulnerable. However, this military adventure could jeopardy the recent efforts to build a more developmental State in Chad.